MEDICAMENT PUMPS AND CONTROL SYSTEMS THEREOF - BROWN, Justin, P; LIM, David, Chi-Wai; EL-KHATIB, Firas, H; HENDERSON, David, Matthew; ROSINKO, Michael, J; PATEL, Himanshu (2024)
Ambulatory medicament devices that provide therapy to a subject, such as blood glucose control, are disclosed. Disclosed systems and methods can implement one or more features that improve the user experience, by modifying delivery of therapy to a subject after determining that a possible occlusion exists in a medicament delivery system, monitoring the status of an ambulatory medical device and the health condition of a subject that receives therapy from the ambulatory medical device and annunciating alarm condition when necessary, selectively muting alarm annunciations while a Do Not Disturb mode is activated, implementing various power saving modes to save power, controlling operation of the device and medicament delivery based on the user gesture controls, and controlling medicament delivery based on a condition of the ambulatory medicament device.